Determination of the mechanical properties of anterior column units and functional spinal units of the l3-l4 lumbar porcine segment (2014)
Porcine specimens have proven to be an excellent option for experimental studies of the spine, due to the anatomically and biomechanically similarities with that of the human; however, there are differences that should be taken into account when comparing both specimens. The objective of this study is to determine the stiffness coefficient of the L3-L4 lumbar porcine segment by means of axial compression tests performed on Anterior Column Units (ACU’s) and Functional Spinal Units (FSU’s), in order to compare the results obtained with the information found in the literature for the human case. The results showed that the FSU's support approximately 22% more load compared to ACU's, which approximates to the 18% found for the human case. It can be concluded that characteristics such as the vertebrae morphometry has a direct impact on the mechanical properties of the ACU’s and the FSU’s.